2009
DOI: 10.1016/j.cellbi.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Upstream reactive oxidative species (ROS) signals in exogenous oxidative stress‐induced mitochondrial dysfunction

Abstract: Exogenous oxidative stress induces cell death, but the upstream molecular mechanisms involved of the process remain relatively unknown. We determined the instant dynamic reactions of intracellular reactive oxygen species (ROS, including hydrogen peroxide (H(2)O(2)), superoxide radical (O(2)(*)(-)), and nitric oxide (NO)) in cells exposed to exogenous oxidative stress by using a confocal laser scanning microscope. Stimulation with extracellular H(2)O(2) significantly increased the production of intracellular H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It has been recognized that mitochondrial dysfunction appears to promote ROS production (Lu and Gong, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that mitochondrial dysfunction appears to promote ROS production (Lu and Gong, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…One commonly used oxidant, hydrogen peroxide (H 2 O 2 ) is freely diffusible within the cell and causes a wide range of effects based on concentration and cell type, including an increase in mtDNA damage compared to nDNA damage (nuclear DNA) [3,4,6,22,23], mtDNA degradation [10], increased mitochondrial mass [24], cell growth arrest [3,25-29], apoptosis [6,29-31], autophagy [31], increased secondary ROS such as H 2 O 2 and superoxide [32], and decreased antioxidant activity [33,34]. However, the only study linking oxidative stress to a decrease in mitochondrial function is a 2001 study by Szweda and Nulton-Persson, which suggested that H 2 O 2 treatment of isolated rat heart mitochondria caused a reversible decline in oxidative phosphorylation [34].…”
Section: Introductionmentioning
confidence: 99%
“…ROS generation in cisplatin-treated hair cells was closely correlated with its ototoxicity. An increased ROS will cause a decrease of mitochondrial membrane potential, which alters cellular energy production and starts mechanisms for the execution of apoptosis [20,23]. Our results showed that exposure to cisplatin (20 μM) for 6 h increased the generation of ROS in hair cells and about a two-fold increase in ROS production 48 h after cisplatin exposure.…”
Section: Resultsmentioning
confidence: 68%
“…Mitochondrial ROS burst is an early upstream apoptotic signal. Oxidative damage to mitochondria causes the impairment of mitochondrial function and subsequently leads to cell death via apoptosis and necrosis [2022]. Therefore, we investigated the level of ROS in organ of Corti explant using DCFH-DA.…”
Section: Resultsmentioning
confidence: 99%